Angular-polarization multiplexing with spatial light modulators for resolution enhancement in digital holographic microscopy. (3rd April 2017) - Lai, Xin-Ji; Cheng, Chau-Jern; Lin, Yu-Chih; Tu, Han-Yen
Abstract: This work presents an angular and polarization multiplexing technique for synthetic aperture (SA) imaging in digital holographic microscopy by using a pair of phase-type spatial light modulators (SLMs) to achieve resolution enhancement through a single hologram acquisition. Angular multiplexing is applied to adjust the incident wave propagation at different specific deflection angles by modulating a SLM panel as a binary phase grating. The other SLM panel is introduced to control the polarization of the propagating object beams and thus ensure orthogonal polarization between these waves to avoid mutual interference of the conjugated first-order diffracting beams derived from the same phase grating. Experimental results indicate that the spatial resolution and signal-to-noise ratio of the reconstructed image are efficiently improved. Furthermore, an electrically addressed SLM pair creates the possibility to perform a dynamic and precise manipulation for realizing angular-polarization multiplexing SA imaging without the use of mechanical scanning mirrors.